Peripheral nerve repair throughout the body with processed nerve allografts: Results from a large multicenter study. Issue 5 (26th February 2020) - Safa, Bauback; Jain, Sonu; Desai, Mihir J.; Greenberg, Jeffrey A.; Niacaris, Timothy R.; Nydick, Jason A.; Leversedge, Fraser J.; Megee, David M.; Zoldos, Jozef; Rinker, Brian D.; McKee, Desirae M.; MacKay, Brendan J.; et al.
Abstract: Background: Peripheral nerve damage resulting in pain, loss of sensation, or motor function may necessitate a reconstruction with a bridging material. The RANGER® Registry was designed to evaluate outcomes following nerve repair with processed nerve allograft (Avance® Nerve Graft; Axogen; Alachua, FL). Here we report on the results from the largest peripheral nerve registry to‐date. Methods: This multicenter IRB‐approved registry study collected data from patients repaired with processed nerve allograft (PNA). Sites followed their own standard of care for patient treatment and follow‐up. Data were assessed for meaningful recovery, defined as ≥S3/M3 to remain consistent with previously published results, and comparisons were made to reference literature. Results: The study included 385 subjects and 624 nerve repairs. Overall, 82% meaningful recovery (MR) was achieved across sensory, mixed, and motor nerve repairs up to gaps of 70 mm. No related adverse events were reported. There were no significant differences in MR across the nerve type, age, time‐to‐repair, and smoking status subgroups in the upper extremity ( p > .05). Significant differences were noted by the mechanism of injury subgroups between complex injures (74%) as compared to lacerations (85%) or neuroma resections (94%) ( p = .03) and by gap length between the <15 mm and 50–70 mm gap subgroups, 91 and 69% MR, respectively ( p = .01). Results were comparable to historical literature for nerve autograft and exceed that of conduit. Conclusions: These findings provide clinical evidence to support the continued use of PNA up to 70 mm in sensory, mixed and motor nerve repair throughout the body and across a broad patient population.